From Cultural Context to Tourist Routes: A GIS-Based Approach to Enhancing Interpretive Strategies by Tour Guides - Yenny Susanto; Andri Machmury; Indra Gunawan (Journal of Economic Education and Entrepreneurship Studies, 2024)
This study investigates the interpretative strategies employed by tour guides in Takalar Regency to manage cultural specificity as spatially-based tourism content. Utilizing a qualitative and ethnographic approach, the research involved direct observations, interviews with tour guides, and spatial data analysis through Geographic Information Systems (GIS). Key findings reveal that tour guides effectively use interpretative techniques to convey the richness of local culture, including traditions such as Songkabal, Attoana Karaeng, Balla Lompoa, Akkaleo’ Dodoro, and Tradisi Patorani. While these strategies are successful for domestic tourism, challenges remain in attracting international visitors. Mapping tourist movement patterns indicates a preference for efficient travel routes, suggesting a need for more integrated tourism route development. In conclusion, enhancing interpretative content relevance and employing GIS to design optimal tourism routes could significantly improve tourist experiences and promote sustainable tourism growth in Takalar Regency.